Temperature Monitoring via the Internet of Things Using PID-iTCLab - Basuki Rahmat; Minto Waluyo; Tuhu Agung Rachmanto (Future Science, 2022)
iTCLab or Internet-Based Temperature Control Lab is a temperature control kit for feedback control applications with an ESP32 Microcontroller, LED, two heaters, and two temperature sensors. The heater power output is adjusted to maintain the desired temperature setpoint. Thermal energy from the heater is transferred by conduction, convection, and radiation to the temperature sensor. Heat is also transferred from the device to the environment. In this paper, it is shown how to program temperature monitoring on the iTCLab Kit via the Internet of Things (IoT) using the Arduino programming language. The controller used is Proportional Integral and Derivative (PID). From the experimental results, the temperature monitoring system works well, and the results of temperature control via a cellphone using the IoT MQTT Panel are shown by the real situation